La relocalisation de l’agriculture : entre dimension spatiale et représentations des acteurs. Le cas des circuits courts collectifs - Julien Frayssignes; Michaël Pouzenc; Valérie Olivier-Salvagnac (Développement Durable et Territoires)
The recent development of agri-food network is characterized by a profusion of initiatives with diverse modes of organization. These initiatives all avail themselves of a processus of relocation of agriculture. However, even if the relocation is envisaged through a closeness between producers and consumers, the concept remains poorly defined, by an overinvestment of social aspects and a mobilization of too broad topics. The article aims at proposing a formalization of the concept, through the reintegration of spatial and productive dynamics, and the deepening of the question of perception of relocation by stakeholders. The reflection thus allows to question the perenniality of these collective agri-food networks and their capacity to play a structuring role for agriculture.